Remarkable complexity and variability of corticospinal tract defects in adult Semaphorin 6A knockout mice - Mitchell, Kevin (My University, 2019)
The corticospinal tract (CST) has a complex and long trajectory that originates in the cerebral cortex and ends in the spinal cord. Semaphorin 6A (Sema6A), a member of the semaphorin family, is an important regulator of CST axon guidance. Previous studies have shown that postnatal Sema6A mutant mice have CST defects at the midbrain–hindbrain boundary and medulla. However, the routes the aberrant fibers take throughout the Sema6A mutant brain remain unknown. In this study, we performed 3D reconstruction of immunostained CST fibers to reevaluate the details of the abnormal CST trajectories in the brains of adult Sema6A mutant mice. Our results showed that the axon guidance defects reported in early postnatal mutants were consistently observed in adulthood. Those abnormal trajectories revealed by 3D analysis of brain sections were, however, more complex and variable than previously thought. In addition, 3D analysis allowed us to identify a few new patterns of aberrant projections. First, a subset of fibers that separated from and descended in parallel to the main bundle projected laterally at the caudal pons, subsequently changed direction by turning caudally, and extended to the medulla. Second, some abnormal fibers returned to the correct trajectory after deviating substantially from the original tract. Third, some fibers reached the pyramidal decussation normally but did not enter the dorsal funiculus. Section immunostaining combined with 3D reconstruction is a powerful method to track long projection fibers and to examine the entire nerve tracts of both normal and abnormal animals.
Keywords: corticospinal tract (CST); semaphorin family; midbrain–hindbrain boundary; 3D reconstruction; Axon guidance; Corticospinal tract; Knockout mouse; Semaphorin 6A